Information Circular 34. Precambrian Geology of the Southern Canadian Shield and the Eastern Baltic Shield - Ojakangas, Richard W. (Minnesota Geological Survey, 1991)
U.S.A.-U.S.S.R.-Canada Joint Seminar, August 21-23, 1990, Duluth, Minnesota The geologic histories of the Canadian and Baltic Shields in North America and Europe, respectively, are broadly similar, and the topic was discussed during a conference and field trip involving North American and Russian participants in the late summer of 1990. During a two-day meeting prior to the field trip, twelve North American and eleven Soviet geologists presented papers, and participants discussed a variety of problems and ideas in Precambrian stratigraphy, sedimentology, tectonics, magmatism, industrial minerals, and metallogeny. Special emphasis was placed on problems of correlation. All papers were simultaneously interpreted by Senior Translator and Interpreter Grigori Sokolov of the Institute of Geology, Karelian Branch, U.S.S.R. Academy of Sciences, who accompanied the Russian delegation. His ability contributed greatly to the meeting's success. In addition to the speakers, thirty-eight geologists attended the conference: four Canadians, two Finns, and thirty-two Americans, including eight graduate students. As a result of the seminar and field trip, exciting and promising opportunities for continued cooperation were identified. Specific proposed activities include meetings, field excursions, short courses, joint publications, individual research-oriented exchanges, and joint projects. Involvement of young geologists was especially encouraged to promote long-term cooperative relationships. Opportunities also were identified for cooperation with other international projects, such as existing bilateral programs and the International Geological Correlation Program. It was mutually agreed that in 1991-1992, the Institute of Geology, Karelian Research Center, and the Kola Research Center of the USSR Academy of Sciences will host conferences and field trips on Proterozoic and Archean geology and metallogeny in the eastern Baltic shield. In 1991, the field program will emphasize Proterozoic geology, and in 1992, Archean geology. Other joint activities in the future will depend on the outcome of the 1991 and 1992 meetings. It was the intent of the organizers to bring this joint activity to the attention of officials involved in relevant international programs. Toward that end this proceedings volume has been published by the Minnesota Geological Survey. The body of this report consists of two parts; the first is a series of short papers that provide an overview of the Precambrian geology in the Great Lakes Region; the second part consists of a similar overview of the eastern part of the Baltic Shield. Convened with the support of United States National Science Foundation (N SF-INT -9000365) Geological Survey of Canada University of Minnesota, Duluth, Department of Geology Minnesota Geological Survey Ontario Geological Survey Union of Soviet Socialist Republics Academy of Sciences Soros Foundation-Soviet Union